Desarrollo de una aplicación android como módulo independiente de facturación electrónica para un negocio que se encuentre calificado como pequeña y mediana empresa (PYME) - Moreta Trujillo, Wellington Gutember (2017)
The present investigation project is carried out by means of the analysis of the billing process that is currently handled in most businesses, including those that are considered as small and medium companies (SME), the latter to which development is focused, An independent module of electronic invoicing, which will be delivered to the Salesian Polytechnic University to exercise their respective copyright. As a first step for this project, the objectives under which the theoretical content research is obtained, obtained from reliable sources of information, were identified, thus strengthening the knowledge about the electronic invoicing process and the applications required for its experimentation and development. Based on the selected methodology, the requirements for project implementation were identified, allowing the adoption of good practices to manage each stage of development, ensuring in this way compliance with both the parameters specified for billing and customer expectations final. The following phase of the project specified the tools and technologies required to ensure a correct exchange of information between the regulator, which in this case is the SRI (Internal Revenue Service), and the end user, thus achieving an adequate functioning. Finally, each of the components of the system are described with their respective definition and purpose, thus detailing the complete operation of the module, which was subjected to several tests for the acceptance of the final product by the user.